Impacts of urbanization on renewable energy consumption in China. (15th February 2016) - Yang, Jun; Zhang, Wei; Zhang, Zongyi
Abstract: In this paper, we used the logarithmic mean Divisia index method to investigate the impact of urbanization on renewable energy consumption growth (RECG). The growth in renewable energy consumption is attributed to the urbanization effect, energy mix effect, energy intensity effect, economic effect, and population effect; RECG can be roughly divided into the slow growth stage, the fluctuant growth stage, and the accelerated growth stage. The results showed that the energy mix effect, economic effect, and population effect positively affected RECG. However, a significantly negative relationship was found between energy intensity and RECG. Furthermore, the contribution of urbanization differed in RECG stages, and urbanization contributed more to the total energy consumption growth than to RECG. This study would thus provide policymakers with insights about the link between urbanization and renewable energy consumption.